The Freer-Logion (Mark 16:14): GA 032, Jerome, and Erasmus. - Burnet, Régis; Clivaz, Claire (TC: A Journal of Biblical Textual Criticism, 2023)
As regularly noted, the Freer-Logion has not often been studied until today. Its reference by Jerome in Pelag. 2.15 is mentioned, but New Testament scholars have overlooked its first modern commentator, Erasmus, until three 2022 and 2023 articles by Krans, Yi, and Burnet. As a next step, this article presents the first French and English translations of the complete Annotationes of Erasmus on Mark 16:14 next to the Latin text edited by Hovingh (2000). We demonstrate that his philological notes are particularly fruitful for understanding the history of Mark's ending. Using the term coronis, in the sense of the end of a given unit, Erasmus asserts that the sentences quoted by Jerome have been inserted into chapter 16 and may have come from an apocryphal source. We suggest that the addition after Mark 16:3 in VL 1 can also be seen as a coronis inserted in Mark 16. Finally, we discuss the κορωνίς drawn at the end of Mark in GA 032: this editorial decoration adds supplementary evidence for a fifth-century date for the copy of Mark in W, as proposed by Orsini (2019).